Depressive Disorder, Anxiety Disorder and Chronic Pain: Multiple Manifestations of a Common Clinical and Pathophysiological Core (2016)
Introduction: A high proportion of depressive disorders are accompanied by anxious manifestations, just as depression and anxiety often present with many painful manifestations, or conversely, painful manifestations cause or worsen depressive and anxious expressions. There is increasingly more evidence of the pathophysiological, and neurophysiological and technical imaging similarity of pain and depression. Methods: Narrative review of the pathophysiological and clinical aspects of depression and chronic pain comorbidity. Research articles are included that emphasise the most relevant elements related to understanding the pathophysiology of both manifestations. Results: The pathological origin, physiology and clinical approach to these disorders have been more clearly established with the latest advances in biochemical and cellular techniques, as well as the advent of imaging technologies.